Global Call to Action: maximize the public health impact of intermittent preventive treatment of malaria in pregnancy in sub-Saharan Africa - Chico, R Matthew (Malar J, 2015)
Intermittent preventive treatment of malaria in pregnancy is a highly cost-effective intervention which significantly improves maternal and birth outcomes among mothers and their newborns who live in areas of moderate to high malaria transmission. However, coverage in sub-Saharan Africa remains unacceptably low, calling for urgent action to increase uptake dramatically and maximize its public health impact. The ‘Global Call to Action’ outlines priority actions that will pave the way to success in achieving national and international coverage targets. Immediate action is needed from national health institutions in malaria-endemic countries, the donor community, the research community, members of the pharmaceutical industry and private sector, along with technical partners at the global and local levels, to protect pregnant women and their babies from the preventable, adverse effects of malaria in pregnancy.